Percutaneous Mitral Valvuloplasty Using the Double Balloon Technique: Immediate Results and Determinant Factors of Increasing Mitral Regurgitation - Park, Seung-Jung (Korean J Intern Med, 1991)
Percutaneous mitral valvuloplasty (PMV) was successfully performed in 112 (95%) out of 118 patients (32 M, 80 F, mean age: 38±11 years) with mitral stenosis. There was a significiant increase in the mitral valve area (MVA) from 0.9±0.2 to 2.0±0.7 cm(2) p<0.0001, a decrease in the mean mitral gradient from 17±6 to 6±3 mmHg, p<0.001, and a rise in cardiac output from 4.3±0.8 to 4.8±1.2 L/min, p<0.001. The morphologic features of the mitral stenosis was evaluated using echocardiographic score. Patients with a low-score (≤8) had more effective dilation of mitral stenosis compared to patients with a high-score over 8 (0.9 to 2.2 vs 0.8 to 1.6 cm(2), p<0.001), despite the similar EBDA/BSA (effective balloon dilating area/body surface area). The patients with good results after PMV (MVA ≥ 1.5 cm(2)) were more likely to be in normal sinus rhythm (p<0.0001), younger age (p<0.001), smaller left atrial size (p<0.05), and lower total echoscore (p<0.002), especially in leaflet mobility (p<0.02) and degree of calcification (p<0.002), compared to patients with relatively poor result after PMV (MVA < 1.5 cm(2)). There were no differences in EBDA/BSA, calcification on fluoroscopy, and history of previous surgical commissurotomy between the 2 groups. Mitral regurgitation (MR) developed or increased in severity in 41 (37%) cases. The patients with an increase in MR had relatively smaller initial MVA (p<0.001) and more thickened valve leaflets (p<0.02). Although there was an increasing trend in total echoscore and EBDA as the severity of the MR increased, those were statistically not significant. Complications included embolic episode in 3 (3%), cardiac tamponade in 3 (3%), and creation of ASD (Qp/Qs≥1.5) in 22 (20%). Thus this data suggest that valvuloplasty using the double-balloon technique is a safe and effective procedure in selected patients; mitral valve dilation was more effective in younger patients with normal sinus rhythm, smaller left atrium, more mobile and less calcified valve leaflets and lower total echoscore; and an increase in MR after valvuloplasty appeared to be related to initial mitral valve area and valvular thickening.